2009
DOI: 10.1186/1423-0127-16-32
|View full text |Cite
|
Sign up to set email alerts
|

Effects of statins on the secretion of human serum albumin in cultured HepG2 cells

Abstract: Statins reduce cholesterol biosynthesis by inhibiting HMG-CoA reductase and thereby lower total cholesterol and LDL cholesterol levels in serum, which in turn lower the incidence of cardiovascular disease (CVD). Statins are also known to modulate various cellular functions such as gene expression, cell proliferation, and programmed cell death through inhibition of downstream intermediates in cholesterol synthesis. In this study, we have investigated the possible effects of statins on the secretion of serum alb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 36 publications
1
14
0
Order By: Relevance
“…Furthermore, the different MTSs may affect the cleavage and dimerization of the protein and therefore its activity as well. As the TAT‐MTS‐MCM fusion proteins enhanced various mitochondria characteristics, such as ATP levels, oxygen consumption and mitochondrial membrane potential, we could conclude that the mitochondria play a major role in the pathology of MMA, confirming other reports .…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, the different MTSs may affect the cleavage and dimerization of the protein and therefore its activity as well. As the TAT‐MTS‐MCM fusion proteins enhanced various mitochondria characteristics, such as ATP levels, oxygen consumption and mitochondrial membrane potential, we could conclude that the mitochondria play a major role in the pathology of MMA, confirming other reports .…”
Section: Discussionsupporting
confidence: 89%
“…In the process of cell expansion, it is crucial to ensure that the expanded cells maintain their physiological functions. Albumin secretion capacity can be used as a way to evaluate the quality of liver‐like cells and to reflect their activity . In this study, the concentration of albumin secreted into the supernatant was measured for cells grown in different microcarriers.…”
Section: Resultsmentioning
confidence: 99%
“…20 A vast majority of cardiovascular surgery patients receive statin therapy, which in addition to reducing HMG-CoA, have also been shown to stimulate albumin secretion from hepatocytes. 21 Furthermore, albumin participates in cholesterol efflux from peripheral tissues and contributes to the overall cholesterol efflux along with contributions from high-density lipoproteins. Analyses from 14,571 cardiac surgery patients between 1992 and 2005 found that extremely obese patients (BMI ≥45kg/m 2 ) have higher perioperative morbidity and mortality compared with a lower BMI group (BMI 24 – 34.9kg/m 2 ).…”
Section: Discussionmentioning
confidence: 99%